Vertical changes in abundance, biomass and community structure of pelagic polychaetes down to 1000 m depths at Station K2 in the western subarctic Pacific Ocean covering the four seasons and day–night. (3rd May 2021) - Amei, Kanako; Dobashi, Ryo; Jimi, Naoto; Kitamura, Minoru; Yamaguchi, Atsushi
Abstract: Pelagic polychaetes are distributed from the sea surface to greater depths of the oceans worldwide, but little information is available regarding their ecology. This study investigated the vertical distribution of abundance, biomass and community structure of pelagic polychaetes at a single station in the western subarctic Pacific based on day–night vertical stratified samples collected from a 0 to 1000 m water column during four seasons covering 1 year. The polychaete abundance and biomass ranged from 0 to 757 ind. 1000 m −3 and 0–6.1 mg WW m −3, respectively. Ten pelagic polychaete species belonging to nine genera and six families were identified. From cluster analysis based on abundance, the polychaete community was divided into five communities. Each community occurred at different depth layers. Two surface groups seen at 0–200 m were dominated by two carnivorous species: Tomopteris septentrionalis and Typhloscolex muelleri . The deepest group, dominated by the particle feeder Pelagobia longicirrata, was seen at 500–1000 m. Two transition groups occurred in the intermediate depths. These vertical distributions of the pelagic polychaete communities were common throughout the season and day. Water mass, food availability and the oxygen minimum layer are put forth as environmental factors that affect the pelagic polychaete community.